Methods in Banach Space Theory 2006
DOI: 10.1017/cbo9780511721366.003
|View full text |Cite
|
Sign up to set email alerts
|

Saturated extensions, the attractors method and Hereditarily James Tree Spaces

Abstract: Contents 0. Introduction 1 0.1. Hereditarily James Tree spaces 3 0.2. Saturated extensions 7 0.3. The attractors method 10 1. Strictly singular extensions with attractors 15 2. Strongly strictly singular extensions 24 3. The James tree space JT F2 . 32 4. The space (X F2 ) * and the space of the operators L((X F2 ) * ) 40 5. The structure of X * F2 and a variant of X F2 46 6. A nonseparable HI space with no reflexive subspace 52 7. A HJT space with unconditionally and reflexively saturated dual 63 Appendix A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 15 publications
0
56
0
Order By: Relevance
“…For an arbitrary seminormalized weakly null sequence in Z X we can pass to a subsequence satisfying the same (1), (2) and (3) as in the proof of Proposition 7. Since Remark 2 is the same are Remark 1 with a different quotient map, by mimicking the proof of Proposition 7 it can be shown that this subsequence in Cesaro summable, as required.…”
Section: Proof Let E ⊂ N Be An Interval and (Bmentioning
confidence: 99%
See 3 more Smart Citations
“…For an arbitrary seminormalized weakly null sequence in Z X we can pass to a subsequence satisfying the same (1), (2) and (3) as in the proof of Proposition 7. Since Remark 2 is the same are Remark 1 with a different quotient map, by mimicking the proof of Proposition 7 it can be shown that this subsequence in Cesaro summable, as required.…”
Section: Proof Let E ⊂ N Be An Interval and (Bmentioning
confidence: 99%
“…In [2] a Banach space Z is constructed satisfying the assumptions of Theorem 21. Z * is the desired space.…”
Section: Spaces Not Admitting Quotients With Separable Dualsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, if X is QHI restricted to block-subspaces, then no quotient of X by an FDD-block subspace can contain an unconditional basic sequence, and therefore X must contain a quotient of a subspace with the stronger "angle zero" property. [1], the distinction between general quotient spaces and quotients by FDD-block subspaces may be essential: there exists a separable dual space X with a Schauder basis such that quotients with w * -closed kernels are HI, yet every quotient has a further quotient isomorphic to l 2 . Since FDD-block subspaces of X are w * -closed, this space has the restricted QHI property, but it is not QHI by the l 2 -saturation property.…”
Section: Remarks and Open Questionsmentioning
confidence: 99%